Estimation of Critical Loads and Low-Cycle Fatigue of Laminated Plates with Delamination Regions - Kowalczyk, H.; Ochelski, S. (Engineering Transactions, 1997)
The results of experimental investigation into the problem of effects of delamination on the critical load and the low-cycle fatigue of a laminated plate are presented. The rectangular plates tested were composed of epoxy-glass composite facings and a core of foamed polyvinyl chloride, with circular delaminations between one of the two facings and the core.